Pembuatan Paku Payung Panjang 50 mm, Diameter 2,5 mm, Tebal Pelat Payung 1,2 mm Kapasitas 300 Biji/Jam (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The problem lies in the quality of the umbrella nails for asbestos or zinc roofs which often experience damage to the nail head is not large enough, the tip of the nail is blunt, thus damaging the roof material, and susceptibility to corrosion due to weather, and slow manual production. The purpose of making is to obtain umbrella nails with a length of 50 mm and a diameter of 2.5 mm which are strong, pointed tips, relatively fast. The manufacturing method includes: making cylindrical umbrella pieces from 2 mm thick aluminum with a diameter of 25 mm and a 1.5 mm hole center, selecting raw materials for low carbon steel wire, AISI 1020 in the form of a 3 mm diameter coil, straightening and reducing the cross-section of wire using a die (wire drawing),, forming the nail head (cold heading), mechanically cutting the pointed end, forming the nail umbrella from cylindrical pieces that have been inserted with 50 mm long nails and pressed, immersing the umbrella nails in 500oC zinc liquid (galvanizing) for 2 minutes, checking dimensions and quality standards. The manufacturing results are in the form of strong zinc-coated thumbtacks measuring 50 mm in length, 2.5 mm in diameter, 1.2 mm in thickness of the thumbtack plate, total production cost of IDR 340/unit, and process duration of 12 seconds/unit, which implies that the need for strong and corrosion-resistant thumbtacks can be met for various related engineering needs.